Health Communication during the COVID-19 Pandemic: Visitors' Perceptions of Health Protocols at Sentra Grosir Cikarang Market (Oratio Directa, 2022)
This qualitative descriptive case study examines health communication and visitors' perceptions of mask use, handwashing, and physical distancing at Sentra Grosir Cikarang Market during the COVID-19 pandemic. Data were collected through interviews, observation, and documentation from ten informants aged 16-47, including visitors, one market manager, and one lecturer. The source does not report the fieldwork period, sampling strategy, interview guide, consent procedure, or detailed triangulation results. Findings show mixed perceptions. Some participants regarded masks as protective, while others associated them with breathing discomfort. Handwashing was supported as protection from germs, but was sometimes avoided because of reported skin sensitivity or the belief that no contact had occurred. Distancing was constrained by crowding and narrow market space, although visiting during quieter hours enabled compliance. Communication used direct reminders and printed media, but knowledge, habit, comfort, infrastructure, and environmental conditions shaped responses. The study recommends consistent, persuasive, dialogic communication supported by accessible facilities. Because the evidence is limited to one case and summarized accounts, it cannot establish compliance rates or intervention effectiveness.
Keywords: Health communication; Public perception; Health protocols; Traditional markets; COVID-19